THE CONTRIBUTION OF MUSEUMS’ DIGITALIZED PALAEONTOLOGICAL COLLECTIONS TO THE SCIENTIFIC LITERACY OF COMPULSORY EDUCATION STUDENTS: THE CASE OF AN INTERACTIVE MULTIMEDIA PRODUCTION OF THE PALAEONTOLOGICAL AND GEOLOGICAL MUSEUM OF THE UNIVERSITY OF ATHENS - Fermeli, G.; Dermitzakis, M. (Bulletin of the Geological Society of Greece, 2010)
The aim of the current paper is to present an interactive trilingual multimedia production, which designed in order to support school students’ scientific literacy; as well as to enhance them the awareness, provision of information and education mainly in matters of palaeontology. In order to achieve scientific literacy, school students, must interact with scientific objects and data and must experience the role of interpretation and analysis in problem solving activities. The current production, based on a part of the digitized collections of the Palaeontological and Geological Museum of the University of Athens, offers this opportunity to the school students. The application is a stand-alone learning environment and is divided into two parts. In the first part, there are presented the key geological concepts and the second part comprises interactive educational activities. Through an environment that promoted the development of observation skills, quest for information, decision-making procedures, critical thinking and systematization and following the spiral development of the material, there have been designed two sets of activities: one - for Primary and one - for Secondary education